A Narrative Review of Lifestyle Risk Factors and the Role of Oxidative Stress in Age-Related Hearing Loss - Diana Tang; Yvonne Tran; Piers Dawes; Bamini Gopinath (Antioxidants, 2023)
Age-related hearing loss affects a significant proportion of adults aged 60 years and above, with a prevalence of 65%. This condition has a negative impact on both physical and mental well-being, and while hearing interventions can help alleviate the effects of hearing loss, they cannot completely restore normal hearing or halt the progression of age-related hearing loss. Oxidative stress and inflammation have been identified as potential contributors to this condition. By addressing modifiable lifestyle risk factors that exacerbate oxidative stress, there may be an opportunity to prevent hearing loss. Therefore, this narrative review provides an overview of the major modifiable lifestyle risk factors associated with age-related hearing loss, that is, exposure to noise and ototoxic chemicals, smoking, diet, physical activity, and the presence of chronic lifestyle diseases, and offers an overview of the role of oxidative stress in the pathophysiology of this condition.